Basics of Optimization Strategy for Integrating Space Industry Technology Package Into Global Value Chains - Omelyanenko Vitaliy (Economics and Business)
The article deals with basic characteristics and fundamentals of innovation management of global value chains and considerations on the example of space industry based on the factor of interaction in the creation of new products in global value chains. General context of global value chains as a factor of strategy development and characteristics and factors of global value chains in space industry is considered. Mechanism of the development of space engineering as global industry at the national level is proposed. The author proposes to consider four groups of level of characteristics of the competitiveness of technological component for integration into the global value chain of space industry projects.